PEMBENTUKAN JARINGAN EKONOMI PELABUHAN MAKASAR AWAL ABAD KE-19 - Huddy Husin (Sosio e-Kons, 2015)
The development of community wich living in maritime, with socio-economic activity can not be separated from the existence of local potential, it is manifested from the ability to organizing the existence of communities along coast of Makassar. It will be more visible when the coastal communities to respond the local and international shipping network. Besides the dynamic economic activities along the coast of South Sulawesi is inseparable from the existence of social structures, and becoming basic building of socio-economic activities, further the socio-structures become a key to driving ann moving the maritime history, especially in around the coast of South Sulawesi. Keyword : Economic Network, Port of Makassar